2018
DOI: 10.1007/s11882-018-0764-z
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Manifestations of Reactions to Biologics

Abstract: Anti-TNF agents and immune checkpoint inhibitors have significant, immune-mediated cutaneous manifestations that can necessitate discontinuation. Anti-TNF agents, IL-6 inhibitors, and IL-12/23 inhibitors can paradoxically cause psoriasis flares or unmask previously undiagnosed psoriasis. IL-17 inhibitors are unique in increasing risk for Candida infections. Benign injection site reactions, non-specific rash, cellulitis, and hypersensitivity reactions are relatively common adverse events. A wide variety of cuta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 141 publications
0
4
0
Order By: Relevance
“…Common adverse effects of ustekinumab include headaches, fatigue, abdominal pain, and upper respiratory infections 2 . Few cutaneous side effects have been reported 3 . Although there was concern that the drug might increase the risk of nonmelanoma skin cancer because of blockade of IL-12 antitumor activity, clinical data have not shown this to be the case 2, 3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Common adverse effects of ustekinumab include headaches, fatigue, abdominal pain, and upper respiratory infections 2 . Few cutaneous side effects have been reported 3 . Although there was concern that the drug might increase the risk of nonmelanoma skin cancer because of blockade of IL-12 antitumor activity, clinical data have not shown this to be the case 2, 3.…”
Section: Discussionmentioning
confidence: 99%
“…Few cutaneous side effects have been reported 3 . Although there was concern that the drug might increase the risk of nonmelanoma skin cancer because of blockade of IL-12 antitumor activity, clinical data have not shown this to be the case 2, 3. Multiple immunologically based dermatologic conditions, namely alopecia areata, linear IgA bullous dermatosis, and eczematous and lymphomatoid drug reaction, have been reported in conjunction with this drug 3 …”
Section: Discussionmentioning
confidence: 99%
“…Delayed reactions have also been reported with biologics, including more common reactions such as mild delayed maculopapular eruptions and serum sickness-like reactions (SSLRs). Of the biologic agents discussed in this review, SSLRs have been most frequently reported with rituximab and infliximab, but have also been reported to dupilumab and omalizumab [19][20][21][22][23][24]. Severe cutaneous adverse reactions such as Stevens-Johnson Syndrome/toxic epidermal necrolysis have been reported but are significantly more rare [25,26].…”
Section: Classification Systems Of Adverse Reactions To Biologicsmentioning
confidence: 96%
“…Reported symptoms include pruritus, flushing, hives and rash, and delayed urticaria/angioedema, most likely caused by IgE antibodies directed against non-self peptide sequences in the chimeric structure. 21 Local injection site reactions (Figure 5a) including pain, swelling, erythema, are described for most biologics. 22 In addition to irritation, type IV allergic reactions are also described, but it is not always possible to distinguish between the different reaction types.…”
Section: Mechanism 5: Allergic or Pseudo Allergicmentioning
confidence: 99%